Types of corporate social responsibility actions and their impact on change in return on assets and abnormal returns. - Li, Zhi Liang. (2012)
This study examines the corporate social responsibility (CSR) actions that firms undertake to deal with their CSR concerns. We will also study the effect of the CSR actions on firms’ return on assets and abnormal returns. The analysis is based on an extensive 20-year dataset covering over 3,000 publicly traded firms. We find that CSR strengths are positively correlated with lagged CSR concerns, which means that firms with higher CSR concerns are likely to have higher CSR strengths in future. More than half of the firms do not take any CSR actions with respect to their changes in concerns. Of the remaining firms that take action, a very small portion (11.7%) of them do so directly in the areas where their CSR concern arise, with the remaining firms acting in other areas of CSR instead. Upon controlling for various factors such as size, year, book-to-market ratio, leverage, and industry type, we find that firms which take action (specifically indirect action) with respect to their concerns are more likely to generate higher change in abnormal returns compared to firms which take no action.